Agricultural expansion in the semiarid chaco: poorly selective contagious advance - Volantea, J. N., Mosciaroa, M. J., Gavier-Pizarrob, G. I., Paruelo, J. M. (My University, 2016)
Clearance for agriculture or cattle ranching was the dominant land-cover change during the last two decades in the South American Dry Chaco. The Argentinean portion has been particularly affected, presenting greater deforestation rates than the continental and global averages. Little is known on the control factors of the location and the spatial clearance patterns. In this article we studied (a) deforestation dynamics in the Argentinean Dry Chaco and the factors determining land clearing locations for the last 25 years (b) changes in the relative impact of those factors through time and space and (c) the effect of regulations aimed to control the location and magnitude of land transformation. We also tested the &ldquoexpansion of the agricultural frontier&rdquo hypothesis for the Argentinean Chaco. To identify the factors that defined agricultural expansion we used binomial logistic models that were fitted to a set of independent variables (bio-physical, infrastructure and political factors) that could eventually influence the distribution of new agricultural areas. Results indicate that the Forest Law devised by the Argentinean federal government to control the clearing process was insufficient to restrict both the area transformed per year and clearance locations. Agriculture is expanding over marginal areas and land clearing dynamics have been increasingly associated to the proximity to already cleared areas, defining a frontier&mdashadvancement pattern which gives the idea of a contagion process. According to our results, the relative importance of the anthropic factors associated to the agricultural expansion in the region increased through time. Highlights •We study the deforestation drivers in the Argentine Chaco for 25 years. •We model the way those factors operated through time and space. •We evaluate the effect of regulations controlling the land transformation. •The legal instruments were insufficient to control land clearings. •The relative importance of the anthropic factors increased through time.
Keywords: Deforestation, Land use change, Models, Dry Chaco, Remote sensing